Digital Humanities and Creativity: Intersections - Führ, Fabiane; Bisset Alvarez, Edgar (Advanced Notes in Information Science, 2022)
Scientific articles on digital humanities and creativity indexed in the Dimensions, Scopus and Web of Science databases are analyzed. Term co-occurrence analysis was applied from the abstract section of the papers. We evidenced that 2018 was the most productive year, and the projects are very diverse when it comes to digital humanities topics. Most of the explored themes were related to the use of vlogs and Instagram, application analysis, analysis of the transformation of reading modes, and the social transformation promoted by different teaching strategies and experiences. We consider this topic requires further and deeper exploration.